Increased Clinical Sensitivity and Specificity of Plasma Protein N-Glycan Profiling for Diagnosing Congenital Disorders of Glycosylation by Use of Flow Injection–Electrospray Ionization–Quadrupole Time-of-Flight Mass Spectrometry. (1st May 2019) - Chen, Jie; Li, Xueli; Edmondson, Andrew; Meyers, Gail Ditewig; Izumi, Kosuke; Ackermann, Amanda M; Morava, Eva; Ficicioglu, Can; Bennett, Michael J; He, Miao
Abstract: BACKGROUND: Congenital disorders of glycosylation (CDG) represent 1 of the largest groups of metabolic disorders with >130 subtypes identified to date. The majority of CDG subtypes are disorders of N -linked glycosylation, in which carbohydrate residues, namely, N -glycans, are posttranslationally linked to asparagine molecules in peptides. To improve the diagnostic capability for CDG, we developed and validated a plasma N -glycan assay using flow injection–electrospray ionization–quadrupole time-of-flight mass spectrometry. METHODS: After PNGase F digestion of plasma glycoproteins, N -glycans were linked to a quinolone using a transient amine group at the reducing end, isolated by a hydrophilic interaction chromatography column, and then identified by accurate mass and quantified using a stable isotope-labeled glycopeptide as the internal standard. RESULTS: This assay differed from other N -glycan profiling methods because it was free of any contamination from circulating free glycans and was semiquantitative. The low end of the detection range tested was at 63 nmol/L for disialo-biantennary N -glycan. The majority of N -glycans in normal plasma had <1% abundance. Abnormal N -glycan profiles from 19 patients with known diagnoses of 11 different CDG subtypes were generated, some of which had previously been reported to have normal N -linked protein glycosylation by carbohydrate-deficient transferrin analysis. CONCLUSIONS: The clinical specificity and sensitivity of N -glycan analysis was much improved with this method. Additional CDGs can be diagnosed that would be missed by carbohydrate-deficient transferrin analysis. The assay provides novel biomarkers with diagnostic and potentially therapeutic significance.